Acute and chronic dysimmune polyneuropathies in the context of the COVID-19 pandemic: pathogenesis, features of the clinical picture, diagnosis and therapy (literature review) - A. E. Khrulev; N. A. Shiyanova; S. N. Sorokoumova; D. S. Kasatkin; V. N. Grigoryeva; K. M. Belyakov; E. S. Romanova; D. S. Yankevich (Нервно-мышечные болезни)
Dysimmune polyneuropathies are the etiologically heterogeneous group of diseases with autoimmune damage to the peripheral nervous system. The rarity of these diseases doesn’t exclude the possibility of their development or exacerbation in patients infected with SARS‑CoV‑2, which will require timely differential diagnosis and urgent specific therapy. The article summarizes current information on the mechanisms of development, clinical features, diagnosis and management of acute and chronic dysimmune polyneuropathies in the context of the COVID‑19 pandemic.